The potential of endophytic bacteria from the root of Eucalyptus pellita as a biocontrol agent against Ralstonia solanacearum - Yuliana susanti; GIYANTO GIYANTO; MEITY SURADJI SINAGA; KIKIN HAMZAH MUTAQIN; BUDI TJAHJONO2 (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Susanti Y, Giyanto, Sinaga MS, Mutaqin KH, Tjahjono B. 2021. The potential of endophytic bacteria from the root of Eucalyptus pellita as a biocontrol agent against Ralstonia solanacearum. Biodiversitas 22: 3454-3462. Bacterial wilt disease (BWD) caused by Ralstonia solanacearum is one of the most damaging eucalyptus (Eucalyptus pellita F. Muell.) diseases. However, endophytic bacteria can be utilized to control it. This study aims to obtain and screen endophytic bacteria isolated from the root of eucalyptus as a biocontrol agent against BWD. A pathogenic R. solanacearum was isolated for artificial inoculation; subsequently, isolation, characterization and screening of the potential endophytic bacteria were conducted. Isolates of R. solanacearum demonstrated the pathogenicity for BWD in eucalyptus, with the highest virulence found in Rs 18. In total, 24 isolates of endophytic bacteria were obtained and screened for their biocontrol potential. The endophytic bacteria conveyed the capacity of antibiosis, indole acetic acid (IAA) hormone, nitrogen fixation, phosphate dissolution, protease enzyme and AHL-lactonase, which are the main indicators of bioagent characteristics in endophytic bacteria, as well as being plant growth stimulators. Four isolates were selected with the highest according to the analytic hierarchy process (AHP), identified on the 16S rRNA gene. Most isolates belonged to gram-negative bacteria. The four isolates, namely B33/77 (Serratia nematodiphila), B32/77 (Paenibacillus polymyxa), B13/497 (Brevundimonas olei) and B17/111 (Bacillus megaterium), indicated their potential for biocontrol as plant growth promoters. This study is the first report on the isolation of endophytic bacterial from eucalyptus roots with regard to its benefit as a plant growth promoter. It provides basic information about the characteristics of the endophytic bacteria, which showed potential as a biocontrol agent of R. solanacearum on eucalyptus.